Cognition Is Not What It Used To Be: Reconsidering Usability from an Embodied Embedded Cognition Perspective - Dijk, Jelle (Human Technology, 2009)
Embodied embedded cognition (EEC) has gained support in cognitive science as well as in human–computer interaction (HCI). EEC can be characterized both by its action-centeredness as well as its roots in phenomenology. The phenomenological aspects of EEC could be seen as support for trends in design emphasizing the user experience. Meanwhile, usability issues often are still approached using traditional methods based on cognitivist assumptions. In this paper, I argue for a renewed focus on improving usability from an EEC perspective. I draw mainly on a behavior-oriented interpretation of the theory, the key aspects of which are reviewed. A tentative sketch for an embodied embedded usability is proposed, doing justice to the embodied embedded nature of interaction while retaining the goal of developing technology that is easy to use in everyday practice.